2014
DOI: 10.1186/2193-1801-3-50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Millettia ferruginea (Birbra) foliage supplementation on feed intake, digestibility, body weight change and carcass characterstics of Washera sheep fed natural pasture grass hay basal diet

Abstract: AbstractsTwenty-four yearling male local Washera lambs with an average initial body weight of 18.14 ± 1.07 kg were used to assess the nutritional value of Millettia ferruginea. Experimental animals were grouped into six blocks of four animals, and each animal was randomly assigned to one of the four dietary treatment feeds. The treatments used were; Sole natural pasture grass hay (T1), and 150, 300, 450 g DM Millettia ferruginea leaf hay with ad libitum natural pasture grass hay assigned for (T2), (T3) and (T4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), acid detergent fiber (ADF) and ash content of mixed grass hay used in the present experiment was almost similar with other authors (Alemu et al, 2014;Gebru and Tesfay, 2017). The DM, CP and ash contents of the commercial feeds: noug seed cake, sesame cake and wheat short were comparable with previous studies (Gebru and Tesfay, 2017;Mekasha et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The dry matter (DM), organic matter (OM), neutral detergent fiber (NDF), acid detergent fiber (ADF) and ash content of mixed grass hay used in the present experiment was almost similar with other authors (Alemu et al, 2014;Gebru and Tesfay, 2017). The DM, CP and ash contents of the commercial feeds: noug seed cake, sesame cake and wheat short were comparable with previous studies (Gebru and Tesfay, 2017;Mekasha et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…The results of the present study indicated that supplementation has a positive effect on most of the edible offal components (Table 2). This is in agreement with the findings of [10,17,18]. Among the edible offal components namely: tongue (P < 0.001), liver with gall bladder and tail (P < 0.01), total fat (omental and kidney) and omaso-abomasum (P < 0.05) were significantly heavier in the supplemented sheep as compared to the non-supplemented sheep.…”
Section: Edible and Non-edible Offal Componentssupporting
confidence: 92%
“…In the current study, among the offal components classed as edible, the weights of liver and reticulo-rumen increased with increase in Mulato II inclusion in the ration. Similarly, Alemu et al (2014) and Gebreyohannes et al (2003) observed significant increase in liver weight with concentrate supplementation. In addition, Lawrence and Fowler (1998) reported an increase in liver weight following supplementation, which they attributed to the storage of reserve substances such as glycogen in the liver in supplemented sheep.…”
Section: Edible and Non-edible Carcass Offalsmentioning
confidence: 78%